STOMATOPHORA MAJUMDARI SP. N. (APICOMPLEXA : SPOROZOA) AN ACEPHALINE GREGARINE IN THE SEMINAL VESICLES OF EARTHWORM OF WEST BENGAL, INDIA - BANDYOPADHYAY, P. K.; ROYCHOUDHURI, U. S.; BISWAS, GARGI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2001)
<span style="color: #000000; font-family: Roboto, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">A new acephaline gregarine, Stomatophora majumdari sp. n. have been described from the seminal vesicles of the earthworm, Metaphire (=Pheretima) posthuma of Krishnanagar, Nadia, West Bengal, India. The shape of the trophozoite is spherical or ovoidal, flattened and compressed between its poles. It measures 40.0-63.4 m in diameter. The gamontocytes are ovoidal. The large and small gamontocytes measure 90.1-130.5 x 0-115.5 um and 49.9-90.0 x 36.6-55.5 pum respectively. The oocyst is navicular measuring 8.0 x 4.8 pum.